Photovoltaic generation system - Eggers Junior, Paulo Ernesto; Palomino Bolıvar, Luis Eduardo (Visión electrónica, 2014)
The photovoltaic generator at Professional Education Center - CEDUP ”Vidal Ramos”, located in the district of Marcilio Dias in Canoinhas SC, Brazil – was installed in 1994 by the company Eletrosul, in the framework of the Energy Development of States and Municipalities Program - PRODEEM – of the federal goverment, which have educational purposes pointed for the students and teachers learning of these center in the forms of alternative generation and renewable energy. This article reports the results of comparative research in the case where the system of power generation considered other configurations, in particular: photovoltaic modules, the connection between the battery bank to the charge controllers, voltage inverter, and load. The proposed configurations allow to consider new details to optimize project results in generation of electricity from solar energy conversion with photovoltaic panels.